Особливості соціально-економічного розвитку Польщі після вступу до Європейського Союзу - Мандрик, І. П.; Mandryk, I. P. (Східноєвропейський національний університет імені Лесі Українки, 2014)
Проаналізовано динаміку основних макроекономічних показників сoціaльнo-екoнoмічнoгo рoзвиткy Пoльщі за 2003–2012 рр. Визначено позитивні зрушення в розвитку економіки країни після вступу до ЄС. Визначено основні прoблеми сoціaльнo-екoнoмічнoгo рoзвиткy Пoльщі після вступу до ЄС.

The dynamics of the main macroeconomic indicators of social and economic development of Poland in the 2003–2012 years has been analysed. Positive changes in the development of the country's economy after accession to the EU were defined. The main problems of social and economic development of Poland after accession to the EU have been revealed.
Peculiarities of the Social and Economic Development of Poland After Accession to the European Union
Keywords: соціально-економічний розвиток; Польща; Європейський Союз; social and economic development; Poland; European Union